2021
DOI: 10.32601/ejal.911149
|View full text |Cite
|
Sign up to set email alerts
|

The predictive role of morphological awareness and productive vocabulary knowledge in L2 postgraduate students’ academic writing

Abstract: Studies have found that morphology awareness could assist writers to increase productive vocabulary (e.g. Green et al., 2003;McCutchen & Stull, 2015), reduce vocabulary errors (e.g. Karakas, 2012;Ririn, 2010), and produce complex sentence structures using various forms of words. Postgraduate students as second language users of English (L2) were found to experience lack of vocabulary and have difficulties in their academic writing. Researchers have been concentrating on examining the relationship of morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…For example, McCutchen and Stull (2015) concluded that morphology awareness was useful in assisting writers to increase productive vocabulary; Asaad and Shabdin (2021) drew the conclusion that morphological awareness significantly correlated with academic writing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, McCutchen and Stull (2015) concluded that morphology awareness was useful in assisting writers to increase productive vocabulary; Asaad and Shabdin (2021) drew the conclusion that morphological awareness significantly correlated with academic writing.…”
Section: Discussionmentioning
confidence: 99%
“…vocabulary (McCutchen & Stull, 2015). Asaad and Shabdin (2021) observed that morphological awareness significantly correlated with academic writing, helping students to produce texts and convey ideas meaningfully. Vincy (2020) built in such elements in the supplementary teaching materials developed for the experimental group as contextual introduction of the target vocabulary; focusing on the form; pictorial representation of the meaning of the target word; most frequent derivatives of the word; and creating a means for emotional association with the word meaning.…”
Section: Morphology Awareness Was Also Pinpointed To Be Useful In Ass...mentioning
confidence: 99%
“…According to Cameron (2001: 72), developing a practical vocabulary is critical to learning a foreign language at the fundamental level. Besides, the capacity of L2 writers to choose the right word to convey their semantic intention will be improved as their vocabulary grows (McCutchen & Stull, 2015), cited in Qasem, H., Asaad, M., & Shabdin, A. A.…”
Section: The Importance Of Vocabulary In Promoting Writing Skillsmentioning
confidence: 99%
“…Many studies on vocabulary L2 have shown the importance of having adequate words that can be used in the target language productively [5][6][7][8][9]. College learners have different goals to succeed academically [10].…”
Section: Introductionmentioning
confidence: 99%